MODELS OF IMPLEMENTATION OF ARTICLE 12 OF THE CONVENTION ON THE RIGHTS OF PERSONS WITH DISABILITIES (CRPD) : PRIVATE AND CRIMINAL LAW ASPECTS - Domański, Maciej; Lackoroński, Bogusław (ROUTLEDGE, 2023)
This book examines the implications of Article 12 of the UN Convention on the Rights of Persons with Disabilities (CRPD), its resulting standard of protection for persons with disabilities and the way it is understood and implemented in its diverse signatory states. Its overarching theme is to assess the impact of CRPD Article 12 on the private law concept of legal capacity and its limitations, the significance of which carries over into the realm of penal law regulations. Its impact is analysed primarily from the legal point of view, but with due regard for its psychological and psychiatric ramifications. Recognising the importance of these disciplines is important when implementing CRPD Article 12 into domestic law, as they contribute to the determinants in creating a qualificatory legal framework for all, persons with disabilities in particular, to exercise their rights to legal capacity without let or hindrance. As active legal capacity is a notion rooted in and coming from private law, this forms the main research perspective. The first section discusses the foundational concepts constituting the CRPD Article 12 standard from domestic private law and international law perspectives. The work shows that the concepts adopted in private law interact with the protection of persons with disabilities as victims provided for in criminal law. In addition, where relevant, authors also look at public law institutions that are connected with the private law solutions. The volume will be an essential reference for academics, researchers and policy-makers working in the areas of private law, criminal law, mental health law, human rights, discrimination law as well as psychology and psychiatry.
Keywords: Convention on the Rights of Persons with Disabilities and Optional Protocol -- (2007 March 30); People with disabilities -- Legal status, laws, etc. -- Europe.; LAW / General